The impacts of hydropower and mining on water quality: an example from the Nam Ngum catchment, Lao PDR - Kallio, M. (CGIAR Research Program on Water, Land and Ecosystems, 2018)
Water quality can be thought of as a measure of the suitability of water for a particular use based on selected physical, chemical, and biological characteristics. The water quality of rivers and lakes changes with the seasons and geographic areas. There is no single measure that constitutes ‘good’ water quality. For example, water suitable for drinking can be used for irrigation, but water used for irrigation may not be suitable for drinking. Typically, water quality is measured against standards for particular uses. Thus, water for drinking needs to be of very high quality, but water used for transport does not need to be of high quality at all. Very poor quality water can be highly toxic to life. Water of this kind may be contaminated with chemicals, pollution and/or pathogens, rendering it poisonous to fish and other aquatic organisms; trees and other vegetation along river banks; and to humans who may come into contact with it or consume it. Industrial waste and sewerage and common sources of water contamination. Because all life depends on water, its quality is therefore essential to sustaining it. Water quality is closely linked to the surrounding environment and land use. Unless it is in vapour form, water is never ‘pure’, and is affected by community uses such as agriculture, urban and industrial use, and recreation. The modification of natural stream flows by dams and weirs can also affect water quality. The weather, too, can have a major impact. The water quality of rivers is generally best in the headwaters, where rainfall is often plentiful. As they travel into lowland areas, however, they encounter areas of high human activity, and quality typically deteriorates. Rivers frequently act as conduits for pollutants by collecting and carrying wastewater from catchments to the ocean. Storm water can also carry heavy loads of nutrients, organic matter and pollutants into streams, rivers, lake, and, eventually, the ocean. Evaluating water quality typically focuses on the following indicators: • Biological: bacteria, algae. • Physical: temperature, turbidity and clarity, colour, salinity, suspended and dissolved solids. • Chemical: pH, dissolved oxygen, biological oxygen demand, nutrients (including nitrogen and phosphorus), organic and inorganic compounds (including toxins). • Aesthetic: odours, taints, colour, and floating matter. • Radioactive: alpha, beta and gamma radiation emitters. Clearly, if the quality of water is too poor to sustain life, then it is a major problem. Water resources are of major environmental, social and economic value everyone, and if water quality becomes degraded this resource will lose its value. Water quality is important not only to protect public health: water provides ecosystem habitats, is used for farming, fishing and mining, and contributes to recreation and tourism. If water quality cannot be maintained, then the uses for which we need it cannot be met.